Kaszubi polscy a wybrane populacje europejskie - genetyczne podobieństwa i różnice - Budnik, Alicja (Polskie Towarzystwo Antropologiczne, 1996)
On the basis of allele frequencies of two blood group systems: ABO and Rh (locus D), the mutual genetic similarities and differences between the Kashubians from Hel Peninsula and Pomerania and the rest of population from Poland and inhabitants of the Baltic countries have been evaluated. Genetic analysis was accompanied by demographic measures delining the degree of isolation of the two Kashubian groups and other Poles living contemporarily, and in the 2nd half of the 19'1' century.
Polish Kashubians and chosen European populations - genetic similarities and differences